1989
DOI: 10.1083/jcb.109.5.2139
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal crypt stem cells possess high levels of cytoskeletal-associated phosphotyrosine-containing proteins and tyrosine kinase activity relative to differentiated enterocytes.

Abstract: Abstract. Growth and differentiation of stem cells is thought to be regulated by growth factors and responding protein tyrosine kinase activities. Comparing mitotic stem cells from the adult intestinal epithelium, isolated from the crypts of Lieberkuhn, with isolated differentiated absorbtive cells we find major differences in the levels of phosphotyrosine-containing proteins. Crypt stem cells possess two major phosphotyrosine-containing polypeptides of 36 and 17 kD which have greater than 15 times more phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…These results are consistent with immunofluorescent images which show that all major actin cytoskeleton proteins are present at their full abundance and are concentrated in the apical enterocyte cytoplasm, even in cells with only a rudi- mentary BB (Fath et al, 1990;Heintzelman and Mooseker, 1990). Although the cytoskeletal protein levels remain con stant, the levels of luminal membrane enzymes such as oligosaccharidases, peptidases and alkaline phosphatase (Weiser et al, 1986) and the level of phosphotyrosine-containing proteins (Burgess et al, 1989) change dramatically as enterocytes migrate to the upper crypt and onto the villus. These changes, among others, have been noted in isolated villus cell fractions and confirm the validity of the cell iso lation paradigm for quantitating changes in cytoskeletal protein expression during enterocyte differentiation.…”
Section: Brush B O R D Er a S S E M B L Y In In Te S Tin A L C R Yptssupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with immunofluorescent images which show that all major actin cytoskeleton proteins are present at their full abundance and are concentrated in the apical enterocyte cytoplasm, even in cells with only a rudi- mentary BB (Fath et al, 1990;Heintzelman and Mooseker, 1990). Although the cytoskeletal protein levels remain con stant, the levels of luminal membrane enzymes such as oligosaccharidases, peptidases and alkaline phosphatase (Weiser et al, 1986) and the level of phosphotyrosine-containing proteins (Burgess et al, 1989) change dramatically as enterocytes migrate to the upper crypt and onto the villus. These changes, among others, have been noted in isolated villus cell fractions and confirm the validity of the cell iso lation paradigm for quantitating changes in cytoskeletal protein expression during enterocyte differentiation.…”
Section: Brush B O R D Er a S S E M B L Y In In Te S Tin A L C R Yptssupporting
confidence: 82%
“…and/or endocytosis. Perhaps the dramatic increase in microvillar height during differentiation results from the increased addition of membrane due to the high tyrosine kinase activity in maturing crypt cells (Burgess et al, 1989).…”
Section: Role Of Kinases In Intestinal Developmentmentioning
confidence: 99%
“…Interestingly, Burgess et al (30) observed that crypt stem cells from chicken intestine have proteins with 15 times more phosphotyrosine than do differentiated absorptive cells located at the tip of the villus. We find that the in vitro protein kinase activity of pp60csrc from the crypt cells is about 8 times higher than that from the cells at the tip of the villus (C.A.C., W.E., S. Mamajiwalla, and D. R. Burgess, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine kinases in the intestinal epithelium act as growth factor receptors and oncogenes. However, whereas we ) and others (Burgess et al 1989;Cartwright et al 1993;Mamajiwalla and Burgess 1995;Marian et al 1989;Raid et al 1993) have previously studied the role of tyrosine phosphorylation in the regulation of intestinal epithelial cell motility and proliferation, the manner in which tyrosine phosphorylation influences intestinal epithelial differentiation has not been thoroughly evaluated. Activation of oncogenes such as pp60c-src may be an important event in colon carcinogenesis, and src activity is known to be increased in less differentiated intestinal crypt cells compared with intestinal villus tip cells (Cartwright et al 1993).…”
Section: Introductionmentioning
confidence: 93%